INSECT OILS - GIRAL, MARIA LUISA; GIRAL, JOSE; GIRAL, FRANCISCO (Laboratorio de Estudios Médicos y Biológicos, CD MEXICO, DF, MEX, 1943)
First described by Greville from Hong Kong, 1866, this alga has gradually spread (or gradually come to light) from many regions It was unknown from the Atlantic until 1903, when collected from the estuary of the Elbe, later extending throughout the coast
CIENC MEX
Keywords: INSECT OILS; MULTIDISCIPLINARIA; ETOLOGIA; INSECTOS